Association between allergic rhinitis, eosinophilia and helminth infection in Alwasliyah Berastagi elementary school students (Talenta Publisher, 2019)
Introduction Eosinophils can regulate local immune and inflammatory responses, and their accumulation inside blood and tissue has long been associated with parasitic infestation and allergic inflammation. The prevalence of allergic rhinitis and helminth infection in children relatively increases every year. The burden of allergic rhinitis and helminth infection is mainly attributed to the quality of life of those infected. The latest study shows that an increase in eosinophil progenitors is important in diseases associated with eosinophilia. Objective: The community service was established to find the distribution of allergic rhinitis, eosinophilia, and helminth infection among students in Alwasliyah Berastagi Elementary School and to determine the association between allergic rhinitis and eosinophilia in helminth infection. In addition, this service is also aimed at increasing student’s knowledge about the association between allergic rhinitis and eosinophilia in helminth infection and how to prevent it. Method: We did the ENT examination, routine blood test, and routine stool examination to 43 students and gave the students education about the association between allergic rhinitis and eosinophilia in helminth infection and how to prevent it. Result: The prevalence of allergic rhinitis, eosinophilia, and helminth infection was 53.5%, 19.5%, and 13%. The highest prevalence of allergic rhinitis is among 11 years old age group and female students (52.5%, 60.9%). The highest prevalence of eosinophilia is among 11 and 12 years old age group both accounting 37.5%. The highest prevalence of helminth infection is in 10 and 12 years old age group (66.7%, 33.3%). Both eosinophilia and helminth infection are higher among male than female students (62.5% and 66.7%). There were more students with a corrected answer that we classify as good knowledge after they were educated than before they were educated. (93% vs 79.1%) Conclusion: There was no significant association between allergic rhinitis, helminth infection, and eosinophilia (p = 0.587 and p = 0.458, p >0.05).